Wine Astringency: More Than Just Tannin–Protein Interactions - Osorio-Lira, F (John Wiley and Sons Ltd, 2022)
Red wines are characterized by their astringency, a very important sensory attribute that affects the perceived quality of wines. Three mechanisms have been proposed to explain astringency, and two theories describe how these mechanisms work in an integrated manner to produce tactile sensations such as drying, roughening, shrinking and puckering. The factors involved include not only tannins and salivary proteins, but also anthocyanins, grape polysaccharides and mannoproteins, as well as other wine matrix components that modulate their interactions. These multifactorial interactions could be responsible for different sensory responses and therefore need to be further studied. This review presents the latest advances in astringency perception and its possible origins, with special attention on the interactions of components, their impact on oral perception and the development of astringency sub-qualities. Future research efforts should concentrate on understanding the mechanisms involved as well as on the limiting factors related to the conformation and stability of the tannin–salivary protein complexes. © 2021 Society of Chemical Industry. © 2021 Society of Chemical Industry.